Air curtain design for cold room / Abdul Muthalib Abdul Ghani - Abdul Ghani, Abdul Muthalib (2023)
The project work is to design the air curtain to maintain the cold room temperature in the range of -28 °C by employing Computer Fluid Dynamic (CFD) in the conceptual design. Besides the calculated design method, this project attempts to utilize CFD technology, effectively acquiring the design result and user-friendly for fabricator to utilize it. The design must also consider the standard specification in order to fulfill the desire requirement. The conceptual design of the air curtain for the cold room will be compare the available parts specification that is available in the market to ensure that it can be fabricate with the available equipments in the market. Thus this has given the opportunity to understand the integration of design theory, especially in design engineering